(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of dysphagia among patients with acute stroke at Vinmec Times City International General Hospital in 2025. Methods: Cross-sectional study. Results: The prevalence of swallowing disorders in stroke patients at Vinmec Times City International General Hospital in 2025 was as follows: severe swallowing disorders accounted for 51.7%, moderate swallowing disorders for 15.8%, and mild swallowing disorders for 2.5%. The majority of patients required complete assistance in daily living activities (76.2-77.4%); in communication (57.1%); and in basic motor activities (81%). Conclusion: The prevalence of dysphagia among stroke patients at Vinmec Times City International General Hospital, in 2025 was notably high. In addition, language and communication disorders were observed in a considerable proportion of patients, significantly impacting their quality of life.